Methodological considerations for assessing elder mistreatment of older adults with cognitive impairment: A scoping review protocol - Karen E. Schlag; Rebecca Czyz; Monique R. Pappadis (PLoS ONE, 2025)
Elder mistreatment (EM) of older persons with cognitive impairment is thought to be grossly underestimated in part due to communication barriers experienced by victims and a lack of consistent screening and reporting, which can skew current understandings of this problem. To improve EM risk and prevalence screening in relation to cognitive impairment, it is important to understand specific approaches for implementing assessment tools and interventions for members of this population. Accordingly, this scoping review (OSF registration osf.io/759k3) will identify, summarize, and compare methodological considerations adopted in studies assessing EM risk and occurrence among older persons with varying degrees of cognitive impairment. Through mapping out existing strategies and approaches used to develop, test, and implement EM screening tools or interventions, this review will outline previously identified recommendations and challenges pertinent to future EM assessment, reduction, and prevention efforts. We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines and apply the Arksey and O’Malley (2005) scoping review framework. We will identify relevant studies by comprehensively searching electronic databases, including Ovid (Medline), Cumulative Index of Nursing and Allied Health Literature (CINAHL), Cochrane Trials (CENTRAL), and Elsevier’s Scopus. Reference lists of included studies will also be examined. For article selection, we will use Covidence software to guide a two-step process of title/abstract and full article screening, which will allow us to identify eligible studies based on our inclusion and exclusion criteria that follows the Study Design, Data, Methods, Outcomes (SDMO) framework. A standardized data extraction tool will be used to collect information related to authors, year of publication, research objectives, sample and study design characteristics, measures, analysis, outcomes, limitations, and study conclusions and implications related to cognition. Data will be analyzed using a thematic approach and presented through the reporting of descriptive statistics and summaries.